Author Response: An International Perspective on Preceding Infections in Guillain-Barré Syndrome: The IGOS-1000 Cohort. (31st January 2023) - Leonhard, Sonja E.; van der Eijk, Annemiek A.; Willison, Hugh J.; Jacobs, Bart C.
Abstract : We thank the readers for their comments on our article. 1 The results of the International Guillain-Barré syndrome (GBS) Outcome Study (IGOS) do not reflect GBS statistics worldwide. We focused on 5 pathogens consistently associated with GBS in case-control studies and found similar distributions across participating countries including Bangladesh, Malaysia, and Japan. 1 In 59% of patients, no evidence of infection was found, which suggests other triggers.